CALCULATION RESULTS OF HEAT-ENERGY PARAMETERS IN STATIONARY MODE OF MODERN HELIO-GREENHOUSES - Fatillayev, Sardorbek; Ergashev, Shaxriyor; Uzakov, Gulom (Innovatsion texnologiyalar, 2024)
The article presents the method of calculating the heat load of modern solar greenhouses and the analysis of the results. The seasonal change of the heating power required for the heater in the greenhouses with polyethylene film and polycarbonate glass cover was studied depending on the outdoor air temperature and solar radiation. In a greenhouse with a useful area of 100 m2, the maximum value of heat load is 18.0 kW in a two-layer polyethylene layer, and 13.0 kW in a polycarbonate coating, that is, it is easier to reduce by 1.38 times, 25-28%.